2016
DOI: 10.1002/ajmg.a.38054
|View full text |Cite
|
Sign up to set email alerts
|

Is cutis verticis Gyrata‐Intellectual Disability syndrome an underdiagnosed condition? A case report and review of 62 cases

Abstract: Cutis Verticis Gyrata-Intellectual Disability (CVG-ID) syndrome is a rare neurocutaneous syndrome characterized by intellectual disability and scalp folds and furrows that are typically absent at birth and are first noticed after puberty. First reported in 1893, the syndrome was mainly identified in subjects living in psychiatric institutions, where it was found to have a prevalence of up to 11.4%. Most patients were reported in the literature during the first half of the 20th century. CVG-ID is now a less rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
0
26
0
4
Order By: Relevance
“…4 Most cases are sporadic, although hereditary cases have been described. 2 The prevalence of CVG is unknown in most South American countries, including Bolivia; however, a Colombian study indicated the prevalence of CVG to be 5.9% among institutionalised patients. 5 Primary essential CVG usually presents in puberty as symmetric scalp folds extending from the vertex to the occiput which cannot be flattened by traction or pressure.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Most cases are sporadic, although hereditary cases have been described. 2 The prevalence of CVG is unknown in most South American countries, including Bolivia; however, a Colombian study indicated the prevalence of CVG to be 5.9% among institutionalised patients. 5 Primary essential CVG usually presents in puberty as symmetric scalp folds extending from the vertex to the occiput which cannot be flattened by traction or pressure.…”
Section: Commentmentioning
confidence: 99%
“…5 Primary essential CVG usually presents in puberty as symmetric scalp folds extending from the vertex to the occiput which cannot be flattened by traction or pressure. [1][2][3] Typically, the folds resemble the brain cortex and extend anteroposteriorly, although they may also occur in a horizontal direction in the occipital region. Biopsies of the folds show normal skin histopathology.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of CVG is unknown. It is categorized as primary essential, primary non-essential, or secondary ( 1 , 2 ) .…”
mentioning
confidence: 99%
“…The secondary form, which can occur at any age, affects men and women with similar frequency; the clinical presentation varies depending on the underlying cause, such causes including cerebriform intradermal nevus, inflammatory dermatoses, endocrine diseases, and genetic syndromes ( 2 , 5 ) . Typically, the scalp folds and furrows seen in CVG show a disordered pattern, with an asymmetric distribution.…”
mentioning
confidence: 99%